The Loving story [videorecording (DVD)] - Buirski, Nancy; Buirski, Nancy; Buirski, Nancy (Docuramafilms : New Video Group, 2013)
On June 2, 1958, Richard Loving and his fiancee Mildred Jeter traveled from Caroline County, VA, to Washington, D.C. to be married. Later, the newlyweds were arrested, tried and convicted of the felony crime of miscegenation. Two young ACLU lawyers took on the Lovings case, fully aware of the challenges posed. The U.S. Supreme Court ruled unanimously in their favor on June 12, 1967 and resulted in sixteen states being ordered to overturn their bans on interracial marriage.